Вегетативне розмноження Sansevieria cylindrica Boj. (Dracaenaceae Salisb.) в умовах оранжерейної культури та культури in vitro - Ivannikov, R.V.; Khejlyk, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Problems of a vegetative reproduction of Sansevieria cylindrica representatives in conditions of ex situ and in vitro are described. It is established, that the vege tative method of reproduction (especially by 20 centimetre cuttings, in autumn) is the more effective for traditional hothouse cultures in conditions of mode rate climate. The technique of the microclonal breeding of this species is optimized. Plantsregene rants are obtained by indirect organogenesis from the callus of leaf explants.